Lega and Five-star Movement voters: exploring the role of cultural, economic and political bewilderment. Issue 3 (2nd September 2018) - Corbetta, Piergiorgio; Colloca, Pasquale; Cavazza, Nicoletta; Roccato, Michele
ABSTRACT: We explore the motivations behind the electoral success of the Lega and the Five-star Movement at the 2018 Italian general election. In most of the literature on populism, the success of the new European populist parties is interpreted as stemming from the process of globalisation, which has produced the so-called 'modernisation losers': 'cultural losers' (people who are disorientated by changes in values, by new waves of migration and by the loss of national sovereignty to the European Union) and 'economic losers' (those for whom the globalisation process has meant economic hardship, downward social mobility and occupational uncertainty). It is these 'modernisation losers' who are claimed to have voted for the populist parties. To this two-fold theoretical hypothesis, we added another: the rise in populism can be explained by the democratic malaise, and particularly by the crisis of mainstream parties, which have steadily lost their function as a link between the people and politics. We analyse the role of these three antecedents of populism – labelled as cultural, economic and political – drawing on 2018 Italian National Election Studies (ITANES: seewww.itanes.org/en ) data. Votes for the Lega were motivated by 'cultural populism', while those for the Five-star Movement could be ascribed to 'political populism', stemming from citizens' growing mistrust – generalised and latent in Western democracies – of political institutions, activated in Italy by favourable structural conditions and external circumstances.